Evaluation of Acemannan in Different Commercial Beverages Containing Aloe Vera (Aloe barbadensis Miller) Gel - Francesca Comas-Serra; Paula Estrada; Rafael Minjares-Fuentes; Antoni Femenia (Gels, 2023)
Aloe vera (Aloe barbadensis Miller) gel is a frequently used ingredient in many food pro-ducts, particularly beverages, due to its reported health benefits. Studies have identified acemannan, a polysaccharide rich in mannose units which are partially or fully acetylated, as the primary bioactive compound in Aloe vera gel. The acemannan content and its degree of acetylation (DA) were measured in 15 different commercial beverages containing Aloe vera at varying concentrations (from 30% to 99.8%) as listed on the label. Other biopolymers such as pectins, hemicelluloses, and cellulose were also evaluated. Flavoured beverages (seven samples labelled as containing from 30% to 77% Aloe vera) presented low levels of acemannan (<30 mg/100 g of fresh sample) and were fully deacetylated in most cases. These samples had high levels of other polymers such as pectins, hemicelluloses, and cellulose, likely due to the addition of fruit juices for flavour. Unflavoured beverages (eight samples, with Aloe vera concentrations above 99% according to their labels) had variable levels of acemannan, with only three containing more than 160 mg/100 g of fresh sample. In fact, four samples had less than 35 mg acemannan/100 g of fresh sample. DA levels in all but one sample were lower than 35%, possibly due to processing techniques such as pasteurization causing degradation and deacetylation of the acemannan polymer. Legislation regarding Aloe vera products is limited, and manufacturers are not required to disclose the presence or quality of bioactive compounds in their products, leaving consumers uncertain about the true properties of the products they purchase.